Modelling the Anisotropic Properties of Grain-Oriented Materials - Martin, Floran; Taurines, Julien; Belahcen, Anouar (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Grain oriented material presents highly anisotropic properties involving both the magnetocrystalline anisotropy and shape anisotropy. Whereas the former is generally well known for iron silicon alloys, the later involves a complex domain decomposition. In this paper, we propose to model the anhysteretic vector properties of grain-oriented steel sheet with a multiscale model. The complexity of the domain decomposition is simplified by a simple shape anisotropy term. The general trend of the measured anhysteretic flux density components can be reproduced by the model.